RNA-Seq Analysis of IL-1B and IL-36 Responses in Epidermal Keratinocytes Identifies a Shared MyD88-Dependent Gene Signature - Swindell, William R.; Beamer, Maria A.; Sarkar, Mrinal K.; Loftus, Shannon; Fullmer, Joseph; Xing, Xianying; Ward, Nicole L.; Tsoi, Lam C.; Kahlenberg, Michelle J.; Liang, Yun; Gudjonsson, Johann E. (Frontiers in Immunology, 2018)
IL-36 cytokines have recently emerged as mediators of inflammation in autoimmune conditions including psoriasis vulgaris (PsV) and generalized pustular psoriasis (GPP). This study used RNA-seq to profile the transcriptome of primary epidermal keratinocytes (KCs) treated with IL-1B, IL-36A, IL-36B or IL-36G. We identified some early IL-1B-specific responses (8 hours post-treatment), but nearly all late IL-1B responses were replicated by IL-36 cytokines (24 hours post-treatment). Type I and II interferon genes exhibited time-dependent response patterns, with early induction (8 hours) followed by no response or repression (24 hours). Altogether, we identified 225 differentially expressed genes (DEGs) with shared responses to all 4 cytokines at both time points (8 + 24 hours). These involved up-regulation of ligands (IL1A, IL1B, IL36G) and activating proteases (CTSS), but also up-regulation of inhibitors such as IL1RN and IL36RN. Shared IL-1B/IL-36 DEGs overlapped significantly with genes altered in PsV and GPP skin lesions, as well as genes near GWAS loci linked to autoimmune and autoinflammatory diseases (e.g., PsV, psoriatic arthritis, IBD, primary biliary cholangitis). Inactivation of MyD88 adapter protein using CRISPR/Cas9 completely abolished expression responses of such DEGs to IL-1B and IL-36G stimulation. These results provide a global view of IL-1B and IL-36 expression responses in epidermal KCs with fine-scale characterization of time-dependent and cytokine-specific response patterns. Our findings support an important role for IL-1B and IL-36 in autoimmune or autoinflammatory conditions and show that MyD88 adaptor protein mediates shared IL-1B/IL-36 responses.